Literasi Kearsipan Keluarga Bagi Siswa-Siswi Sekolah Calon Ayah Ibu - Voettie Wisataone; Rosidah; Nadia Sasmita Wijayanti; Danang Setyaramadani (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The neatness of family archives is still underestimated by the community. A well-managed family archive can provide convenience in finding the family data needed. Negligence in tidying the archives is due to a lack of knowledge and awareness of the community in family archives. This community service provides literacy training on family archives to school of future father and mother’s students. The debriefing was carried out for one month with two stages of implementation. The first stage uses the workshop method, where the service team provides materials and training on procedures for storing archives manually and digitally. Second, using the mentoring method, where participants carry out practice and are directly accompanied by a service team. Of the 19 students who attended the debriefing, 100% stated that the service was very useful and felt that they had an awareness of the family archive. 63% of participants continued to the mentoring stage and 18% of participants were able to complete manual and digital family file fireplaces properly. The process of tidying up family archives requires sufficient time and knowledge so that in the future participants can be given more time so that they can tidy up archives to the maximum.